Heterosis and combining ability analysis for resistance to pod fly and lepidopteran borers in pigeonpea (Cajanus cajan) - LAL, S S; SINGH, I P; JEET, VISHWA (The Indian Journal of Agricultural Sciences, 2013)
A seven-parent diallel (without reciprocal) study was conducted during 1993-95 on the pod fly and lepidopteran borer damage to pigeonpea [Cajanlls cajan (L.) Millsp.) revealed that mean squares due to general and specific combining ability were significant but variance component due to sca was higher than variance component due to gca indicating the predominance of non-additive gene action for inheritance of resislance to pod fly and lepidopteran borers. Parents ’PDA 88-2E’ and ’PDA 89-2E’ were good combiners for pod fly resistance and ’ICP 8860’ and ’Bahar’ were the good combiners for lepidopteran borer rersistance. The crosses ’NP(WR) 15’ x ’PDA 88-2E’, ’DPPA 85-15’ x ’PDA 89-2E’, ’NP(WR) 15’ x ’PDA 89-2E’, ’Bahar’ x ’ICP 8860’, ’DPIA 85-15’ x ’PDA 88-2E’ and ’Bahar’ x ’PDA 88-2E’ were found to be good specific combiner for resistance to pod fly and the cross ’KPBR 80-2-1’ .x ’NP(WR) 15’ was found to be a good specific combiner for resistance to lepidopteran borer. Some of the crosses with high negative values showed high heterotic response over Mid Parent and Better Parent for resistance to pod fly and lepidopteran borer damage.